Clinical Presentation And Etiology of Acute Hepatitis In Children: An Experience From A Tertiary Centre of Bangladesh (Journal of Dhaka Medical College, 2024)
Background: The prevalence of Acute hepatitis is still high in developing countries even though the availability of vaccines, prophylactic measures and improved sanitation.Objective: To investigate clinical features, biochemical parameters and etiology of acute hepatitis among hospitalized children in a tertiary care center.Method: This cross sectional study was conducted in the Department of Pediatrics Dhaka Medical College Hospital between June 2021 to July 2022.A total of 120 children aged bellow 15 years who presented with acute hepatitis were included in the study.Results: Most of the studied children were in 5-10 years age group 73(61%).Most of the children presented with jaundice 112 (93.3%), nausea & vomiting 105(87.5%),low grade fever 73(61%),upper abdominal pain 79(65.8%), pruritus 15(12.5%), melena 12(10%), pale stool 10(8.3%), anicteric 8(6.6%). On physical examination tender hepatomegaly was found 110(91.6%) cases, just palpable spleen 8(6.6%), hepatic encephalopathy 6(5%), ascites 4(3.3%) cases. Among the studied patients 102 (85%) were having herbal or homeopathic medicines at the time of admission. All of patients had increase serum bilirubin and ALT and most of them 79(65.8%) had ALT between 500-1500 IU/L.AST was also raised. Increase prothrombin time/INR 17(14.1%) and low serum albumin was seen in7 (5.8%) cases. Majority cases were HAV 81 (67.5%), followed by HEV 10 (8.3%), non A and non B 9(7.5%), HBsAg & anti-HBcIgM were found with positive 4 (3.3%) cases, HAV with HEV co-infection 3 (2.5%). Other than viral hepatitis Salmonella positive 5(4.1%), drug induced hepatitis due to anti-TB and valproic acid 3(2.5%) cases,3(2.5%) cases Wilson’s disease and 2(1.7%) following Wasp bite.Conclusions: The study found the common presenting features of acute hepatitis were jaundice, anorexia, nausea, vomiting, fever, abdominal pain, tender hepatomegaly and ascites. Acute hepatitis due to HAV was the commonest followed by HEV. Vaccination programme should be taken by government to control hepatitis A in children.J Dhaka Med Coll. 2023; 32(1) : 32-37